Why Microsoft smears-and fears-open source. - Raymond, E.S.
Late in March, Microsoft Corp. escalated its war on open-source code by launching a propaganda campaign aimed at top executives. Through speeches and press conferences it painted Linux and related technologies as ?un-American? and ?a cancer?. The author describes how Microsoft's intention was to persuade software customers not to dare use or even touch open-source code because it might pollute their vital bodily fluids, forcing all their business secrets and proprietary software into the public domain. He argues that this was a ludicrous distortion of reality, as open-source software has been the foundation of the Internet since its beginnings
Keywords: Internet; Linux; Microsoft; Open-source code; Propaganda campaign; Proprietary software; Software customers